Stepwise Differentiation of Mesenchymal Stem Cells Augments Tendon-Like Tissue Formation and Defect Repair In Vivo - Yin, Zi (Stem Cells Transl Med, 2016)
Tendon injuries are common and present a clinical challenge, as they often respond poorly to treatment and result in long-term functional impairment. Inferior tendon healing responses are mainly attributed to insufficient or failed tenogenesis. The main objective of this study was to establish an efficient approach to induce tenogenesis of bone marrow-derived mesenchymal stem cells (BMSCs), which are the most common seed cells in tendon tissue engineering. First, representative reported tenogenic growth factors were used as media supplementation to induce BMSC differentiation, and the expression of teno-lineage transcription factors and matrix proteins was compared. We found that transforming growth factor (TGF)-β1 significantly induced teno-lineage-specific gene scleraxis expression and collagen production. TGF-β1 combined with connective tissue growth factor (CTGF) elevated tenomodulin and Egr1 expression at day 7. Hence, a stepwise tenogenic differentiation approach was established by first using TGF-β1 stimulation, followed by combination with CTGF for another 7 days. Gene expression analysis showed that this stepwise protocol initiated and maintained highly efficient tenogenesis of BMSCs. Finally, regarding in situ rat patellar tendon repair, tendons treated with induced tenogenic BMSCs had better structural and mechanical properties than those of the control group, as evidenced by histological scoring, collagen I and tenomodulin immunohistochemical staining, and tendon mechanical testing. Collectively, these findings demonstrate a reliable and practical strategy of inducing tenogenesis of BMSCs for tendon regeneration and may enhance the effectiveness of cell therapy in treating tendon disorders. SIGNIFICANCE: The present study investigated the efficiency of representative tenogenic factors on mesenchymal stem cells’ tenogenic differentiation and established an optimized stepwise tenogenic differentiation approach to commit tendon lineage differentiation for functional tissue regeneration. The reliable tenogenic differentiation approach for stem cells not only serves as a platform for further studies of underlying molecular mechanisms but also can be used to enhance cell therapy outcome in treating tendon disorders and develop novel therapeutics for tendon injury.